Criminal Threats Against Personnel Control Of Land Without Rights - Arif Nurcahyono; Amin Purnawan (Universitas Islam Sultan Agung, 2020)
The objectives of this research are 1) to find out and explain what is meant by the criminal act of control of land without a power permit or entitled and its elements, 2) Know and explain whether or not the criminal threat is relevant to the perpetrator in accordance with current developments. The results of this study concluded that: 1) Article 6 paragraph (1) letter a of the PRP Act No. 51 of 1960. The criminal act of using land without a permit with the right or legal proxy in the Criminal Code basically contains the following elements: as stellionate. b) It is known that there are other persons entitled to the land; The crime in this article is called Stellionate crime, which means